2021
DOI: 10.1002/rth2.12607
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban in acute venous thromboembolism: UK prescribing experience

Abstract: Background Rivaroxaban was reported as effective as traditional therapies for the acute treatment of venous thromboembolism (VTE) with fewer major bleeding complications in the seminal Einstein program and is now a recommended option for the treatment of VTE around the world. Objective To report the safety and efficacy of rivaroxaban in daily care for the management of acute VTE in the United Kingdom. Patients/Method The FIRST registry is a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The study methodology has previously been reported. 49 The study population for this analysis was the safety population, which included any participant who had received ≥1 dose of rivaroxaban.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methodology has previously been reported. 49 The study population for this analysis was the safety population, which included any participant who had received ≥1 dose of rivaroxaban.…”
Section: Methodsmentioning
confidence: 99%
“…Findings from the FIRST registry demonstrated that rivaroxaban was effective for the majority of patients in daily care. 49 However, 7/1262 (0.6%) reported an episode of VTE recurrence. Five out of those seven cases were as a result of nonadherence to anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, these observational studies differ considerably in design, patient selection, duration of follow‐up, and outcome definitions, limiting generalizability of conclusions. We therefore set out to investigate the methodological and clinical differences across three prospective regional noninterventional registries: the Follow‐up in Rivaroxaban Patients in Setting of Thromboembolism (FIRST) registry in the United Kingdom, 16 , 17 the Register for New Oral Anticoagulants (DRESDEN NOAC) registry in Germany 12 , 18 and the Swiss Venous Thromboembolism Registry (SWIVTER) in Switzerland. 13 We assessed the overall effectiveness and safety of acute VTE treatment with rivaroxaban.…”
Section: Introductionmentioning
confidence: 99%